2011
DOI: 10.1097/mca.0b013e328344b615
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum 8-hydroxy-2′-deoxyguanosine levels with the presence and severity of coronary artery disease

Abstract: In conclusion, the serum 8-OHdG levels are increased in patients with CAD and are associated with the severity of coronary artery stenosis. 8-OHdG might serve as an independent factor for predicting CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 24 publications
3
33
0
Order By: Relevance
“…We also used an ELISA to assess 8‐oxo‐2′‐dG in plasma samples, as conventional chromatographic methods do not have the sensitivity to measure plasma levels. Although the circulating levels of 8‐oxo‐2′‐dG detailed in this study are similar to those reported in cross‐sectional studies using ELISA‐based assays in patients with diabetes mellitus25, 26, 27 and other settings,28, 29, 30, 31, 32 it is understood that ELISA overestimates 8‐oxo‐2′‐dG when compared with high‐sensitivity mass spectroscopy 33. This is partly because of the former method including DNA fragments containing 8‐oxo‐2′‐dG, in addition to free 8‐oxo‐2′‐dG, as well as the presence of interfering compounds in plasma.…”
Section: Discussionsupporting
confidence: 84%
“…We also used an ELISA to assess 8‐oxo‐2′‐dG in plasma samples, as conventional chromatographic methods do not have the sensitivity to measure plasma levels. Although the circulating levels of 8‐oxo‐2′‐dG detailed in this study are similar to those reported in cross‐sectional studies using ELISA‐based assays in patients with diabetes mellitus25, 26, 27 and other settings,28, 29, 30, 31, 32 it is understood that ELISA overestimates 8‐oxo‐2′‐dG when compared with high‐sensitivity mass spectroscopy 33. This is partly because of the former method including DNA fragments containing 8‐oxo‐2′‐dG, in addition to free 8‐oxo‐2′‐dG, as well as the presence of interfering compounds in plasma.…”
Section: Discussionsupporting
confidence: 84%
“…However, there is still a lack of studies evaluating the risk of CAD in women or comparing the two sexes, which also includes studies of the markers of oxidative stress status (5). Recent studies that have explored the relationship between oxidative stress biomarkers and CAD have included women (16)(17)(18)(19)(20)(21)(22)(23)(24), but they are not specifically targeted to exploring cardiovascular physiopathology in female patients. The most important limitation of such studies is the lack of any information on the menopausal status of the women enrolled.…”
Section: Discussionmentioning
confidence: 99%
“…For example, serum 8-OH-2dG levels are significantly higher in patients with coronary artery disease [47] and serum concentrations are higher in patients with diabetes [48]. Increased lymphocyte and serum γH2AX levels were also linked to diseases of accelerated ageing, suggesting that oxidative DNA damage may be a common feature of these diseases [49].…”
Section: Figurementioning
confidence: 99%